Statistical analysis of the men`s European Championships held in Italy 1998 - Czerwinski, J. (Europäischer Handballverband, 1998)
Gathered and described statistical material has provided a lot of information, mainly for coaches. Held in Italy the European Championships confirmed a progress in handball, however more dynamic games would have been appreciated. Most of the matches were played nearly on the same levels, and disposition or mental endurance to a particular game influenced a victory. To properly prepare a team one should take possession of motorial, technical, tactical and motivation tasks; to learn thinking in a game and to solve situations in complex conditions. A player`s tactical perfection should be manifested in a creative processing of previously obtained information in direct sports combat and in performing a prompt, effective action (it gives a spectacular game). Shaping the tactical plan one should have an abundant material of own team as well as opponent`s. In this paper, we have proposed the defence game evaluation based on points, which is, in my opinion, indispensable for overall game analysis. The advantage of this proposal is its simple method, which is valuable theoretically and in practice as well. It is worthy to recall the research contained in "The characterisation of the handball game" from 1996, where the analysis of the top teams was carried out by means of multiple regression with using step algorithm of variable selection. It was proved that sufficient projection of results can be obtained by considering just 3 factors: 1) efficiency of fast attack; 2) efficiency in defence; 3) the number of actions which engage opponent`s defence, after we work out the situation for scoring, so called "assist". The said results should be considered as a valuable advice. Retrospective estimation of the said factors, between our team and the opponent`s, allows to determine (theoretically) the teams in their struggle for a victory. The analysis may be used for preparing feasible tactical plan for a particular match. The European Championships indicated the need of searching for tactical and technical solutions relevant to an attractive game.